Soil carbon efflux and litter decomposition in natural forests of KFRI Peechi campus - Nirajlal K (Academy of Climate Change Education and Research, 2017)
Litter dynamics and soil respiration are of great interest in climate change studies due to their roles in recycling carbon and nutrients. Present study was conducted with the objectives of understanding patterns and the process of litter dynamics and the role of weather on soil carbon efflux. Litterbag technique was used to determine the decomposition of litter for 180 days. Soil CO2 fluxes were measured for a period of three weeks in a month for up to 180 days. Mass loss, total carbon of decayed litter and litter fall were quantified. Major tree species’ litter dynamics were also determined. Relationship between soil CO2 efflux with soil and weather parameters were determined using correlation technique. Decomposition constant with a value of 0.009 day-1 was found in moist deciduous forest. Among weather parameters, soil carbon dioxide efflux had weak positive correlation with rainfall and relative humidity and had weak negative correlation with temperature. Among soil parameters, soil carbon dioxide efflux had very weak positive correlation with soil organic carbon and soil moisture. The weak correlation coefficient value came due to lesser variables which indicates duration of this study is not enough. Among species wise study, Terminalia paniculata possess higher deciduous properties that directly contributing more to soil carbon sequestration and it was also found that Tectona grandis had high carbon content per unit volume compared to other species. But the species Macaranga peltata might sequestered more amount of carbon in a short time due to its high decomposition rate. The study highlights the different responses of soil CO2 efflux to weather and soil parameters but suggests a long duration study for in-depth analysis which is very relevant in carbon dynamics and climate change studies.